Monte Carlo-based quantitative risk assessment of parking areas for vehicles carrying hazardous chemicals. (March 2023) - Li, Yuntao; Wang, Yumeng; Lai, Yuying; Shuai, Jian; Zhang, Laibin
Highlight: A novel quantitative risk assessment method of parking areas for vehicles carrying hazardous chemicals. The proposed method combines a Monte Carlo simulation (MCS) and quantitative risk assessment (QRA). The risk analysis results show that the average risk for centralized parking is lower than that for random parking. A novel parking strategy, called zone parking, is proposed for risk migination. ABSTRACT: During the road transportation of hazardous chemicals, vehicles are often parked in constrained areas. Two main parking strategies have been employed: random and centralized parking. Random parking is difficult to control and may lead to serious casualties, whereas centralized parking increases the likelihood of domino scenarios. Both strategies may have severe consequences. To quantitatively study the risks associated with these parking strategies, a method is proposed here that applies the Monte Carlo simulation (MCS) to quantitative risk assessment (QRA). Numerical simulations yielded the risk distributions for the two parking methods, and analysis was performed. The results show that the average risk for centralized parking is lower than that for random parking; however, high-risk scenarios remain unacceptable. Thus, a novel parking strategy, called zone parking, is proposed. It separates vehicles carrying toxic substances from those carrying flammable and explosive chemicals. The estimated risk for this strategy is significantly lower than for the other two parking strategies. Risk reduction using this zone-parking strategy was validated for detailed case studies. GraphicAbstract: Image, graphical abstract